2003
DOI: 10.1046/j.1365-2036.2003.01746.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: comparative efficacy of different proton‐pump inhibitors in triple therapy for Helicobacter pylori eradication

M. Vergara,
M. Vallve,
J. P. Gisbert
et al.

Abstract: SUMMARYBackground: It is not known whether certain protonpump inhibitors are more efficacious than others when used in triple therapy for Helicobacter pylori eradication. Aim: To compare the efficacy of different proton-pump inhibitors in triple therapy by performing a meta-analysis. Methods: A MEDLINE search was performed. Abstracts of the European Helicobacter pylori Study Group and the American Gastroenterological Association congresses from 1996 to 2002 were also examined. Randomized studies with at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(32 citation statements)
references
References 42 publications
4
28
0
Order By: Relevance
“…The beneficial effects of Lactobacillus-and Bifidobacterium-containing probiotics on the eradication rate and the incidence of total side effects during H. pylori eradication therapy has also been reported in a meta-analysis by Wang et al (29) Hence, the eradication rates obtained in the placebo group in our cohort are consistent with the overall eradication rates reported previously in randomized trials (3,39,44), while the benefit of probiotic therapy on eradication rates also seems to be in agreement with data from studies on probiotics (18,25,29,30,39,(45)(46)(47), including Bifidobacterium (17,42,45).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The beneficial effects of Lactobacillus-and Bifidobacterium-containing probiotics on the eradication rate and the incidence of total side effects during H. pylori eradication therapy has also been reported in a meta-analysis by Wang et al (29) Hence, the eradication rates obtained in the placebo group in our cohort are consistent with the overall eradication rates reported previously in randomized trials (3,39,44), while the benefit of probiotic therapy on eradication rates also seems to be in agreement with data from studies on probiotics (18,25,29,30,39,(45)(46)(47), including Bifidobacterium (17,42,45).…”
Section: Discussionsupporting
confidence: 91%
“…However, similar tendencies of decline in eradication rates have also been reported in recent studies with these alternative regimens because of increased antibiotic resistance as well as increased incidence of undesirable side effects of longer term treatment, which can lead to patient non-compliance (2,3,6,7,(12)(13)(14).…”
supporting
confidence: 58%
“…[4][5][6][7] The literature review showed that the PPIs are a particularly well-tolerated class of drugs. Using this evidence, the DUEC concluded that all PPIs were therapeutically equivalent in efficacy and safety.…”
Section: Description Of the Pharmacy Benefit And Interventionsmentioning
confidence: 99%
“…Systematic reviews have compared clinical efficacy of equipotent doses of available PPIs for symptomatic relief and the maintenance of healing in gastroesophageal reflux disease (GERD), for the healing and maintenance of healing in gastric and duodenal ulcers, and in combination with antibiotic regimens for Helicobactor pylori eradication. [9][10][11] The data consistently support that omeprazole 20 mg is similar in efficacy to lansoprazole (Prevacid) 30 mg, pantoprazole (Protonix) 40 mg, and rabeprazole (Aciphex) 20 mg.…”
mentioning
confidence: 74%